1997
DOI: 10.1097/00007890-199703270-00016
|View full text |Cite
|
Sign up to set email alerts
|

Role of Non-Major Histocompatibility Complex Antigens in the Rejection of Transplanted Myoblasts1

Abstract: Myoblasts obtained from donors histoincompatible for several non-major histocompatibility complex antigens (i.e., including minor histocompatibility antigens) and from syngeneic donors were transplanted without any immunosuppression into the muscles of male dystrophic C57BL/10J mdx/mdx mice. Myoblasts from syngeneic mice resulted in the formation of a high percentage of dystrophin-positive fibers 16 weeks after the transplantation. There was no evidence of a cellular immune reaction against the donor myoblasts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 28 publications
0
13
0
1
Order By: Relevance
“…It was even suggested that this lymphocytic attack not only rejects the hybrid myofibers resulting from the cell transplantation, but also can damage the host myofibers by the "bystander" effect of released cytokines [176]. Incompatibility in minor antigens can also trigger acute rejection of hybrid myofibers, as observed in mice after syngeneic transplantation into females of myoblasts obtained from males [179].…”
Section: The Long-term Survival Of the Myogenic Cell Graftmentioning
confidence: 99%
“…It was even suggested that this lymphocytic attack not only rejects the hybrid myofibers resulting from the cell transplantation, but also can damage the host myofibers by the "bystander" effect of released cytokines [176]. Incompatibility in minor antigens can also trigger acute rejection of hybrid myofibers, as observed in mice after syngeneic transplantation into females of myoblasts obtained from males [179].…”
Section: The Long-term Survival Of the Myogenic Cell Graftmentioning
confidence: 99%
“…Non dystrophin-based alternatives to MTT are designed to avoid this immune problem (see Alternatives and novel approaches below). Interestingly, not only can antibodies to dystrophin be a problem, but host antibodies specific for fetal calf serum, a reagent used in the culture of myoblasts, have been detected in blood samples of mice soon after MTT [32], implicating a long-term detrimental effect of the tissue culture process. This point is addressed further in the following section.…”
Section: Humoral Immunitymentioning
confidence: 99%
“…A quantitative method to analyze MPC survival is a quantitative PCR measurement of Y chromosome expression by the male donor MPC transplanted in the female muscle. 11 Besides being technically not easy and of limited accuracy, this method suffers from an inherited disadvantage of the development of immune response in the female host against the male minor histocompatibility HY antigen expressed in donor cells, as was shown by Boulanger et al 12 The use of mSeAP as a reporter gene presents several advantages. First, the lack of an immune response against mSeAP (unlike lacZ, Luciferase and the Y-chromosome).…”
Section: Introductionmentioning
confidence: 99%